Institutional pluralism and the search for sustainability-oriented innovation opportunities in hybrid organisation forms - Hemel, Stefan Paul Dominik (Cranfield University, 2017)
Organizational search is an inherent part of innovation and enables the creation of new knowledge combinations. It precedes the selection and implementation stages of the innovation management process, which is often concerned with ideas that have commercial potential. There is extensive evidence of global trends that require organisations to innovate in pursuit of sustainable development aims. This transpires a sense of urgency associated with a loss of ecosystem, depletion of natural resources and minerals, climate change and high rates of unalleviated poverty. Such contextual changes call for investigative inquiry into organizations search behaviours for sustainability-oriented innovations (SOI) that privilege open exploration and exploitation of novel sources of value. This more distributed approach to organisational search illustrates venturing in ‘unfamiliar’ territories with so-called ‘unusual partners’. Examples include not-for- profit, no-governmental agencies, civil society and public administrative governmental bodies – as a broader set of stakeholders engaged to identify valuable opportunities for innovation. Search in such collaborations is distinguished from traditional experience, as multiple institutional boundaries are spanned to source new knowledge inputs. These collective endeavours create hybrid organizational forms in which a variety of institutional orders and logics perform. Moreover, they have the capacity to coalesce seemingly competing and antagonistic missions to deliver social, environmental and economic progress. These efforts foster creativity by accessing knowledge and resources from beyond ‘familiar’ territories and boundaries to enhance levels of innovativeness. Recent studies in the field of organizational search have begun to focus on this phenomenon of ‘variety creation’. Such works proffer the merits of organisational boundary spanning behaviours, but to date have been limited to transcending disciplinary, departmental, organisational and sectoral boundaries and knowledge territories. This doctoral study deploys an exploratory detailed case study approach in a market leading multi-national automotive organisation that engages multiple institutional partners for the purposes of innovation. The findings from ten case projects demonstrate that ‘institutional pluralism’ affects the search for SOI opportunities in five major ways. First of all, institutional pluralism provides slack and second, it triggers both local and non-local search types. Third, the relationship between distinct institutional logics promotes different levels of (knowledge) variety creation. Fourth, ‘aligned’ logics have a more positive effect on both variety creation and levels of radicalness. Finally, as the number of logics engaged increases, the range and scope for innovation broadens. The overall theoretical contribution is to the organisation search literature and proposes institutional pluralism as a further mechanism for variety creation. This general contribution has led to further insights concerning the role of slack in local and non- local search variants and logic relationships during the search for innovation opportunities with so-called unusual partners.
Keywords: Organisational search; institutional logics; sustainability-oriented innovation; variety creation; hybrid organisational forms; new knowledge combinations